Exchange Rate Misalignment and Growth : A Myth? - Goncalves, Carlos; Rodrigues, Mauro (Washington, D.C. : International Monetary Fund, 2017)
The impact of real exchange rate movements on GDP growth is a hotly debated issue both in policy and academic circles. In this paper, we provide evidence suggesting that the association between exchange rate misalignment and growth for a broad panel of countries is very weak. Controlling for country fixed effects, time effects and initial GDP, a more depreciated currency is associated with higher growth if one does not exclude outliers. However, this positive association always vanishes after controling for the savings rate. Importantly, this applies for both a large panel of countries and for the emerging economies subsample.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Exchange Rate-Growth Nexus; WP; United States